Residential Segregation and Integration: The Case of Zagreb (Dubrava) - Čaldarović, Ognjen (1997)
New Territorialization of population into the ethnic enclaves has brought about to the new patterns of social integration and social segregation in some parts of Zagreb. Territorial divisions are presently so obvious to make a clear shells, borthers and marks for stronger social divisions of population. It is questionable whether these new divisions are to become new starting points in the development of new forms of social interation or disintegration.
Projekt MZOS
ENG